Evaluation of Science Textbooks for the Elementary Stage According to STEAM Standards - lect.Amir Muhammad Ali Rasool Al-Saadi (Journal of College of Education, 2025)
The study adopted the descriptive analytical approach and involved the development of an analysis instrument consisting of 343 indicators, distributed across 35 standards and 11 domains, based on the Maryland STEM Standards of Practice and the National Core Arts Standards (NCCAS). The content of six science textbooks for Grades 1 through 6 was analyzed using content analysis methodology, with frequencies and percentages extracted for each standard and domain. The results indicated that the level of inclusion of STEAM standards in the science textbooks ranged between 52.48% and 58.31%, reflecting a moderate level of inclusion. The findings also showed that some standards were highly represented while a number of other standards, especially those related to the arts, were either absent or weakly included. The analysis further revealed a disparity in the distribution of standards across the grade levels, along with a clear lack of systematic integration among the STEAM components within the textbook content. In light of these results, the researcher presented a set of recommendations, most notably: the necessity of reviewing and developing the content of science textbooks to enhance the representation of STEAM standards; incorporating and training teachers on implementing integrated education; and building curricula based on clear and coherent standard-based frameworks.